Preliminary molecular phylogeny of beetle cockroaches (Diploptera) and notes on male and female genitalia (Blattodea: Blaberidae: Diplopterinae) - Li, Xin-Ran; Li, Meng; Wang, Zong-Qing (Zootaxa, 2017)
The beetle cockroach, or genus Diploptera Saussure, has been reviewed recently, with unresolved issues remaining. New materials facilitated a molecular phylogenetic study and further comparisons of male and female genitalia among known species. We performed phylogenetic estimates based on two mitochondrial DNA fragments: 657 bases of COI gene and 376 bases of 16S rRNA gene. We used codon model and doublet model (secondary structure) for COI and 16S respectively, and the predicted secondary structure of sequenced 16S fragment is illustrated. The phylogeny revealed that 1) D. bicolor Hanitsch is a junior synonym of D. maculata Hanitsch, and therefore D. pulchra Anisyutkin is also a new synonym of the latter because of its synonymy with D. bicolor; and 2) D. punctata (Eschscholtz) can be reliably determined only for specimens from Hawaii and continental Asia, and distributional records of this species require re-examination. The male phallic complex and female valvulae are generalized with diagrams, and interspecific differences are discussed. Genital structures of Diploptera are not significantly varied. We notice a superficial linkage between hook-like phallomere and pronotum: a protrusion on the inner margin of hook-apex sclerite is combined with an angular pronotum; whilst no protrusion, no pronotal angles. The differences in valvulae lie with the third valvulae and the anterior arch of second valvifer ring; these may have taxonomic implications. The uniformity in physical property of oothecae suggests that all Diploptera species, not only D. punctata, are viviparous.